PARENTING STYLES EFFECT ON CAREER EXPLORATION BEHAVIOR IN ADOLESCENCE: CONSIDERING PARENTS AND ADOLESCENT GENDER - Salim, Rose Mini Agoes; Preston, Melly (Humaniora, 2019)
In facing the industrial 4.0 era, adolescents, especially high school students, need to complement their knowledge and skills learnt from school with behaviors that can help their career journey, namely the career exploration behavior (CEB). Referring to the triadic reciprocal determinism theory and gender role in Indonesian culture, this study aimed to examine the effect of parenting styles and gender on CEB. Specifically, this study examined the effect of paternal and maternal parenting styles on CEB in adolescent and compared its effect on boys and girls. Participants in this study were 427 boys and 397 girls with an average age of 17 from nine high schools. Career Exploration Survey and Parental Authority Questionnaire were used to assess participants? CEB, and paternal and maternal parenting styles. Regression analysis showed different patterns effect of paternal and maternal parenting styles on CEB between boys and girls. For boys, parenting that was found to improve CEB were paternal authoritative parenting and maternal authoritarian parenting, while for girls, parenting that was found to improve CEB were paternal authoritarian parenting and maternal authoritative parenting. These results indicated that boys and girls need different parenting factors from father and mother. Limitation and suggestion are discussed.